2017
DOI: 10.1002/jemt.22851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smear layer removal and marginal adaptation of root canal sealer after final irrigation using ethylenediaminetetraacetic, peracetic, and etidronic acids with different concentrations

Abstract: The purpose of this study was to investigate the effects of different irrigation solutions on the smear layer removal and marginal adaptation of a resin-based sealer to root canal dentine. A total of 152 instrumented roots were irrigated with the following irrigants: 9,18% etidronic acid (HEBP), 0.5, 1,2% peracetic acid (PAA), 17% ethylenediaminetetraacetic acid (EDTA), saline. The amount of smear layer was evaluated using scanning electron microscope (SEM) in seventy root samples.Eighty-two roots were filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 28 publications
5
32
0
2
Order By: Relevance
“…In the present study, the least amount of sealer remnants was observed in the samples irrigated with maleic acid and DualRinse HEDP. The higher smear layer removal capacity of maleic acid and HEBP compared to EDTA has been reported in the previous studies (Ballal et al, 2009;Ulusoy, Zeyrek, & Çelik, 2017). These results can support the present ones, although the chemical composition of tricalcium-silicate cements and smear layer are different.…”
Section: Activation Methodssupporting
confidence: 89%
“…In the present study, the least amount of sealer remnants was observed in the samples irrigated with maleic acid and DualRinse HEDP. The higher smear layer removal capacity of maleic acid and HEBP compared to EDTA has been reported in the previous studies (Ballal et al, 2009;Ulusoy, Zeyrek, & Çelik, 2017). These results can support the present ones, although the chemical composition of tricalcium-silicate cements and smear layer are different.…”
Section: Activation Methodssupporting
confidence: 89%
“…The high surface Gibbs free energy gives rise to low contact angles, which express high wettability of the dentine that facilitates molecular attraction between materials. This explains the lowest gap size values and better marginal adaptation of AH Plus sealer observed on the dentine walls irrigated with HEDP compared with other irrigants (Ulusoy et al 2017), as well as the high push-out bond strength values for the groups irrigated with HEDP (De-Deus et al 2008a, Neelakantan et al 2012. Another example that the components of the dentine surface influence the wettability more than the roughness is the groups with CHX final flushes (G6, G7 and G8).…”
Section: Discussionmentioning
confidence: 93%
“…This explains the lowest gap size values and better marginal adaptation of AH Plus sealer observed on the dentine walls irrigated with HEDP compared with other irrigants (Ulusoy et al . ), as well as the high push‐out bond strength values for the groups irrigated with HEDP (De‐Deus et al . , Neelakantan et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no clear consensus on the sequence of irrigation, the most common protocol is to use sodium hypochlorite (NaOCl) during mechanical preparation to dissolve the organic matter and kill microorganisms, then a strong chelating agent like ethylenediaminetetraacetic acid (EDTA) to remove the smear layer inorganic components and to promote sealer penetration into dentinal tubules (Baca, Junco, Arias‐Moliz, González‐Rodríguez, & Ferrer‐Luque, ; Jardine et al, ; Mancini, Cerroni, Iorio, Dall'Asta, & Cianconi, ; Zehnder, ). Alternatively, the use of a weak chelating agent such as etidronic acid (HEBP) (Tartari et al, ; Ulusoy, Zeyrek, & Çelik, ; Zehnder, Schmidlin, Sener, & Waltimo, ) in combination with NaOCl has been proposed as a single irrigating solution to be used during root canal preparation and as the final solution. The antimicrobial and organic dissolution properties of this combined solution are similar to those of NaOCl alone (Arias‐Moliz, Ordinola‐Zapata, Baca, Ruiz‐Linares, & Ferrer‐Luque, ; Tartari et al, ; Zehnder et al, ), while its advantages during instrumentation are reduced smear layer formation (Lottanti, Gautschi, Sener, & Zehnder, ) and debris accumulation (Paque, Rechenberg, & Zehnder, ).…”
Section: Introductionmentioning
confidence: 99%